ISSUES AND CHALLENGES OF INTEGRATING TOURISM INTO REGIONAL DEVELOPMENT PLANS - Alexandra-Carmen HODISAN; Alina BADULESCU; Elena HERTE (Annals of the University of Oradea: Economic Science)
Development issues have always been considered among the most important challenges in most countries of the world, and especially for poor and developing countries. Tourism being one of the major social and economic phenomena of modern times, it is not surprising that, in theory or practice, tourism is considered as an effective tool for development. Given that development can have different meanings and priorities, depending on the historical, social economic, community or personal context, understanding the role of tourism in the world's economies must also be seen in a broader development perspective, from theory to practice, revealing both its positive effects and negative implications. However, analysis of the literature and practice in the field shows a timid, unconvincing and often uncommitted integration of tourism into development plans at local, regional and national levels. This could postpone or even ignore the essentials of balanced and sustainable economic and social development, aggravating inequalities, perpetuating underdevelopment and negative effects on the environment and the quality of human life, on the natural and cultural-historical values of humanity. In this paper we aim to analyse how tourism can and should be integrated into regional development plans, starting from theoretical considerations on the meaning and significance of economic growth in the literature, the theories and models of growth, and the development objectives in different countries of the world, depending on their level of development or specificities. We have also addressed a regional and local perspective of growth, bringing into discussion tourism as an engine of economic growth and the importance of its integration into regional development plans. We completed our analysis with the main challenges and difficulties of integrating tourism into development models and plans, highlighting relevant solutions and experiences.